Waqf for welfare: A bibliometric analysis of research trends in Scopus-indexed journals - Nonie Afrianty; Asnaini Asnaini; Muthi Adilah Bahril (Faculty of Islamic Economics and Business of Universitas Islam Negeri Mataram, 2024)
Purpose — This study aims to analyze the map and direction of research development in the field of waqf for welfare improvement in Scopus-indexed publications.Method — This research employs a quantitative approach. The population for this study consists of articles indexed by Scopus from 2014 to 2023, with a sample size of 77 articles focused on waqf for welfare improvements. The analysis technique applied in this study involves bibliometric analysis, utilizing the VOSviewer application.Result — The results indicate a rise in the average number of publications per year. The peak productivity in waqf for welfare themes occurred in 2019, with 15 studies identified. In the realm of research on waqf, cash waqf, and Malaysia emerge as the most prevalent themes for welfare improvement. Three clusters were identified: cash waqf for maximizing prosperity in society and economics, the opportunities and threats of cash waqf, and the beneficiaries of waqf, impacting not only individuals but also the state.Novelty — This study represents the first bibliometric review focusing on the specific theme of waqf for welfare development, aiming to fill gaps in existing research.